1997
DOI: 10.1046/j.1365-2141.1997.4003212.x
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐neoplastic drug 5‐fluorouracil produces echinocytosis and affects blood rheology

Abstract: Summary. The anti-neoplastic agent 5-fluorouracil (5-FU) in high therapeutic doses can induce angina pectoris and myocardial infarction. The pathophysiological mechanism of this side-effect has not yet been elucidated. We analysed the influence of 5-FU on blood rheology in vitro. Whole blood, blood cell suspensions and plasma were incubated with increasing concentrations of 5-FU (final concentrations 0, 0 . 08, 0 . 4, 2, 10 and 25 mg/ml 5-FU) at 37ЊC. Erythrocyte morphology was analysed after fixation with glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
(36 reference statements)
1
33
0
Order By: Relevance
“…In vitro studies of red blood cells (RBCs) incubated in 5-FU showed a dose-dependent, reversible transformation of RBCs into echinocytic shape [29,30], which resulted in impaired transit through small pores [29]. Also, alterations in membrane fluidity and RBC metabolism were observed [30-32]: potassium efflux increased [30], oxygen tension ( pO2 ) decreased [31,32], deoxy-hemoglobin levels increased [32], intracellular ATP levels declined and the intracellular 2,3-bisphosphoglycerate (2,3-BPG) concentration rose [31,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies of red blood cells (RBCs) incubated in 5-FU showed a dose-dependent, reversible transformation of RBCs into echinocytic shape [29,30], which resulted in impaired transit through small pores [29]. Also, alterations in membrane fluidity and RBC metabolism were observed [30-32]: potassium efflux increased [30], oxygen tension ( pO2 ) decreased [31,32], deoxy-hemoglobin levels increased [32], intracellular ATP levels declined and the intracellular 2,3-bisphosphoglycerate (2,3-BPG) concentration rose [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Baerlocher et al [29] demonstrated a continuous decrease in blood viscosity with increasing 5-FU concentrations at low shear rates (the rate of change of velocity at which one layer of fluid passes over an adjacent layer) and increasing blood viscosity at high shear rates. 5-FU had no effect on plasma viscosity in this in vitro study [29].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that RBCs may have a role in the transport of chemotherapeutic agents prominent among which are methotrexate (Lena et al, 1987) and 5-fluorouracil (Baerlocher et al, 1997). In this study, we set out to determine whether 667 COUMATE is sequestered into RBCs, as this may explain the high bioavailability of this agent despite its relatively high clearance rate.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 The exact mechanism is currently unclear, but the authors of a systematic review 5 have proposed multifactorial underlying causes, including endothelium-dependent and -independent pathways, direct myocardial damage from cytotoxic effects, induction of apoptosis, rheological side effects, and the production, during drug storage, of cardiotoxic metabolite precursors (for example, fluoro acetate). [6][7][8][9][10][11][12] Animal models of 5-FU cardiotoxicity have manifested apoptosis of myocytes, endothelial cells, or both, which gives rise to clinical presentations similar to that of myocarditis. 12 The toxicity of 5-FU is dependent on the duration of treatment, on the rate of administration, or both; continuous infusions have higher incidences than do bolus regimens.…”
Section: Discussionmentioning
confidence: 99%